2023
DOI: 10.3390/app13116442
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics and Body Image of Japanese Female University Long-Distance Runners

Abstract: While female long-distance runners are considered to have strong body dissatisfaction and body concerns, body-image research that incorporates detailed anthropometric and body composition parameters is still limited. The present study therefore investigates the physical characteristics and body image of Japanese female long-distance runners and explores the factors that influence their body image. Detailed anthropometric and body composition assessment using a dual-frequency bioelectrical impedance analysis (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Height and weight were used to calculate BMI in 25 of 27 studies (92.6%), yet 22 (81.5%) reported relationships between BMI and body image. %BF was evaluated in 11 studies (40.7%); nine (33.3%) used skinfold measurements ( de Sousa Fortes et al, 2013 , 2015a , b , 2020 ; Goltz et al, 2013 ; Mockdece Neves et al, 2016 ; Hernández-Martínez et al, 2017 ; Kagawa et al, 2023 ; Salas-Morillas et al, 2023 ) to estimate %BF, while two (7.4%) utilized DXA ( Eufrásio de Medeiros et al, 2021 ; Remmel et al, 2021 ), and one (3.7%) used dual-frequency BIA (DF-BIA) ( Kagawa et al, 2023 ). A limited number of studies also assessed FFM ( Kagawa et al, 2023 ), lean body mass ( Remmel et al, 2021 ), or fat-free mass index (FFMI) ( Hernández-Martínez et al, 2017 ; Kagawa et al, 2023 ) via DF-BIA, DXA, and skinfold or DF-BIA techniques, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Height and weight were used to calculate BMI in 25 of 27 studies (92.6%), yet 22 (81.5%) reported relationships between BMI and body image. %BF was evaluated in 11 studies (40.7%); nine (33.3%) used skinfold measurements ( de Sousa Fortes et al, 2013 , 2015a , b , 2020 ; Goltz et al, 2013 ; Mockdece Neves et al, 2016 ; Hernández-Martínez et al, 2017 ; Kagawa et al, 2023 ; Salas-Morillas et al, 2023 ) to estimate %BF, while two (7.4%) utilized DXA ( Eufrásio de Medeiros et al, 2021 ; Remmel et al, 2021 ), and one (3.7%) used dual-frequency BIA (DF-BIA) ( Kagawa et al, 2023 ). A limited number of studies also assessed FFM ( Kagawa et al, 2023 ), lean body mass ( Remmel et al, 2021 ), or fat-free mass index (FFMI) ( Hernández-Martínez et al, 2017 ; Kagawa et al, 2023 ) via DF-BIA, DXA, and skinfold or DF-BIA techniques, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the 22 studies (50.0%) assessing an aspect of negative body image had all-female participants ( Karr et al, 2013 ; Voelker et al, 2014 ; de Sousa Fortes et al, 2015b , 2020 ; Aleksic-Veljkovic and Djurovic, 2020 ; Whitehead et al, 2020 ; Eufrásio de Medeiros et al, 2021 ; Godoy-Izquierdo and Díaz, 2021 ; Remmel et al, 2021 ; Jardim et al, 2022 ; Kagawa et al, 2023 ), while four (18.2%) included only males ( Goltz et al, 2013 ; de Sousa Fortes et al, 2015a ; Hernández-Martínez et al, 2017 ; Voelker et al, 2018 ). All but one ( Remmel et al, 2021 ) of these studies reported significant positive associations between BMI, skinfolds or %BF and an aspect of body image disturbance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations